Phospholipase Cγ1 is essential for T cell development, activation, and tolerance - Fu, Guoping (The Rockefeller University Press, 2010)
Phospholipase Cγ1 (PLCγ1) is an important signaling effector of T cell receptor (TCR). To investigate the role of PLCγ1 in T cell biology, we generated and examined mice with T cell–specific deletion of PLCγ1. We demonstrate that PLCγ1 deficiency affects positive and negative selection, significantly reduces single-positive thymocytes and peripheral T cells, and impairs TCR-induced proliferation and cytokine production, and the activation of ERK, JNK, AP-1, NFAT, and NF-κB. Importantly, PLCγ1 deficiency impairs the development and function of FoxP3(+) regulatory T cells, causing inflammatory/autoimmune symptoms. Therefore, PLCγ1 is essential for T cell development, activation, and tolerance.